The infection rate in new diagnosis and relapsed/refractory multiple myeloma patients who had bortezomib-based chemotherapy and relationship between development of infection and lymphocyte/monocyte ratio - Pamukcuoglu, Merve; Baysal, Nuran Ahu; Pepeler, Mehmet Sezgin (The European Research Journal, 2021)
Objectives: Multiple Myeloma (MM) is a disease caused by the clonal proliferation of plasma cells. In recent years, proteozom inhibitors, immunomodulatory agents and monoclonal antibodies have been used in the treatment of MM. In this study, the relation of bortezomib, one of the proteozoma inhibitors used in the treatment of MM, with the development of infection was investigated. Methods: We retrospectively evaluated 56 patients who had MM treated with bortezomib-based regimen. We tried to determine the relationship between infection with immunoglobulin G levels at the time of diagnosis, lymphocyte absolute values at the time of diagnosis, lymphocyte absolute values at the time of chemotherapy, neutrophil absolute value at the time of chemotherapy, lymphocyte absolute values at the time of infection, monocyte absolute value at the time of infection, and the lymphocyte/monocyte (L/M) ratio at the time of infection. The effects of L/M ratio on progression free survival (PFS) and overall survival (OS) were also examined. Results: Thirty (53.6%) of the 56 patients were newly diagnosed, 26 (46.4%) of 56 patients were relapsed/refractory MM. The bortezomib-based regimen was given to all patients. Of the 56 patients included in the study, 21 (37.5%) were female, 35 were male (62.5%). The ages of the patients was 28-79 years (median: 58.5 years). No infection attack was observed in 31 (55.4%) patients. Disease stage (R-ISS) (p = 0.032), presence or absence of co-morbid disease (p = 0.035), disease status during an infection attack (p < 0.01), lymphocytopenia at the time of chemotherapy (p = 0.003), absolute value of lymphocytopenia at the time of infection attack (p < 0.01) and L/M ratio (p < 0.01) had a significant relation with development of infection. Lymphocytopenia at the time of infection attack (p < 0.01, OR<1, 94.6% CI) and L/M ratio (p < 0.01, OR<1, 91.1% CI) had been found significant in univariate logistic regression analysis. Lymphocytopenia at the time of infection attack (p = 0.002, OR<1, 95% CI) and L/M ratio (p = 0.003, OR<1, 95% CI) had been found significant in multivariate logistic regression analysis. L/M ratio had a significant effect on OS (p < 0.017) but not on PFS (p > 0.05). Conclusions: It was determined that L/M ratio has an effect on OS and it is also an independent factor on the development of infection. OS was decreasing and the risk of developing infection was increasing, when the L/M ratio was low.